Efficiency Analysis of Zakat Management Institutions in Banyumas Regency: Case Study of LAZISMU, LAZISNU and BAZNAS - Afief El Ashfahany; Muhammad Iqbal Nur Ishlahudin (Jurnal Iqtisad, 2023)
In the economic field, zakat has a role as an effort to prevent the accumulation of wealth in only one community, therefore must be managed properly.This study focuses on discussing the efficiency of a zakat management institution in Banyumas district. This study discusses two private zakat institutions (LAZISMU Banyumas, and LAZISNU Banyumas) and one Government Zakat institution (BAZNAS Banyumas). This research uses the Data Envelopment Analysis method. This study also uses quantitative methods and uses secondary data types derived from financial report data for 2018, 2019, and 2020 from LAZISMU Banyumas, LAZISNU Banyumas, and BAZNAS Banyumas. The variables used in this research are input and output variables. The input variables consist of assets and operational costs. The output variable consists of collected zakat funds and distributed zakat funds. The results of this study are that in 2018 LAZISMU and LAZISNU experienced inefficiency in the CRS approach, but in the VRS approach the three zakat institutions were efficient. In 2019 LAZISNU experienced inefficiency in the CRS approach, but in the VRS approach.